The Arts, New Literacies, and Multimodality - Albers, Peggy; Harste, Jerome C. (English Education, 2007)
The arts, multimodality, and new literacies studies, each with its own distinct principles, together can redefine literacy and what constitutes being literate. To recognize the roles that each of these fields plays in literacy necessitates a cultural shift in reading, interpreting, creating, and responding to a range of multimedia messages. The everyday literacies that learners bring to the classroom blur the lines between traditional literacy and unpredictable literacy, which promotes reading and writing through multimedia to create morphed and altered texts.
Keywords: arts; literacy; littératie visuelle; media literacy; théâtre